-2(4a-3b)+3(5b-3a)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 16:06:54
-2(4a-3b)+3(5b-3a)-2(4a-3b)+3(5b-3a)-2(4a-3b)+3(5b-3a)由题意得:-2﹙4a-3b)+3(5b-3a)=-8a+6b+15b-9a=-17a+21b
-2(4a-3b)+3(5b-3a)
-2(4a-3b)+3(5b-3a)
-2(4a-3b)+3(5b-3a)
由题意得:-2﹙4a-3b)+3(5b-3a)=-8a+6b+15b-9a=-17a+21b.
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
a+a-a+2a-3a-2b+3b-5b+3b-4b-5b
化简【3A方-(A+B)(B-A)】【4(-B-A)(B-A)+5B方】
(a-b)(a^5+a^4b+a^3b^2+ab^4+b^5)bggg
[(a+b)^-3(a-b)^5/(a-b)^-2(a+b)^4]^2怎么写
5(a-b)-4(a+b)-3(a-b)+2(a+b)怎么算?
(a-b)^2*(b-a)^5+(b-a)^3*(a-b)^4=?
计算:(a+2b)_2(a+2b)+3(a+2b)-4(a+2b)+5(a+2b)-.+99(a+2b)_100(a+2b)
计算:(a+2b)_2(a+2b)+3(a+2b)-4(a+2b)+5(a+2b)-.+99(a+2b)_100(a+2b)
把下列式子化成(a+b)^n或(a-b)^n的形式1.(a+b)^2*(b+a)^3+(a+b)^52.(a-b)^3*(a-b)^2-(a-b)^4*(a-b)+(a-b)^5
(a+3b)(a-3b)-(3a-b)的平方+(4a+5b)·(a+2b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
2a+(4a-5b)-3(a-2b)
计算(5a-3b)^2+(a+b)(a-b)
2a+b/3a+5b 求a/b
等式:(a+b)^0=1 (a+b)^1=a+b (a+b)^2(a+b)^0=1(a+b)^1=a+b(a+b)^2=a^2+2ab+b^2(a+b)^3=a^3+3a^2b+3ab^2+b^3问:(a+b)^4=?(a+b)^5=?``````` (a+b)^9=?
初二分式的加减法2a-b-c/(a-b)(a-c)+ 2b-c-a/(b-c)(b-a)+ 2c-b-a/(c-b)(c-a)3a-6b/a+b- 5a-6b/a-b- 4a-5b/a+b+ 7a-8b/b-a注:有空格的地方是下一个分式